Pengaruh label halal, persepsi keamanan pangan, dan influencer review terhadap keputusan pembelian pada mahasiswa - Arini Noor Khasanah; Lestari Suryaningsih (Journal of Halal Industry Studies, 2026)
Consumers’ purchasing decisions are determined not only by price and product quality but also by halal label, food safety perceptions, and influencer reviews. Accordingly, this study examined the influence of these factors on purchasing decisions. The study aimed to analyze the influence of halal labels, food safety perceptions, and influencer reviews on students’ purchasing decisions. A quantitative, cross-sectional design was employed. The study involved 67 respondents selected using the Slovin formula and the purposive sampling technique. Data were collected via an online questionnaire using a 5-point Likert scale to assess perceptions of the halal label, food safety, influencer reviews, and purchasing decisions. Data were analyzed using SPSS, including validity and reliability tests, classical assumption tests, and multiple linear regression analysis. The results showed that halal labels had a positive and significant effect on purchasing decisions (t=4.45; p<0.05). In contrast, food safety perception (t = -0.38; p > 0.05) and influencer reviews (t = 0.78; p > 0.05) did not have a significant effect on purchasing decisions. Simultaneously, halal label, food safety perception, and influencer reviews significantly influenced purchasing decisions (F = 8.537; P<0.05). These findings suggest that producers should consider including halal labels as a primary means to enhance consumer purchasing decisions.